Choledochal cyst with a twist: Type 1 choledochal cyst and dilated cystic duct with aberrant accessory right hepatic drainage - Pia V. Sodhi; Erin Glennon; Sarah McIntyre; Shailee Lala; Laura Martin; Sandra Tomita (Elsevier, 2023)
Choledochal cysts are rare cystic dilations of the biliary tree that typically involve the extrahepatic bile duct and more infrequently, the intrahepatic bile ducts. Todani's classification of choledochal cysts is the most referenced system in which five types of choledochal cysts are described. Several new variants have been reported including dilations of the cystic duct and a double common bile duct. We describe a never reported variant involving dilation of the common bile duct, dilation of the cystic duct and an accessory right hepatic duct.